AN ECONOMIC STUDY ON THE PROBLEMS AND CHALLENGES OF WOMEN EMPOWERMENT IN PALAYAMKOTTAI, TIRUNELVELI DISTRICT - G.Dhanalakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the problems and challenges faced by women in Palayamkottai, Tirunelveli District, with a focus on identifying the factors impeding their empowerment. Despite various initiatives, women in this region continue to struggle with socio-cultural, economic, and educational barriers. The research aims to examine the socio-economic status of women, identify the challenges they encounter, and suggest measures for improving their empowerment. The findings reveal that gender discrimination, early marriages, lack of education, financial constraints, and family restrictions are significant obstacles. The study recommends promoting adult education, skill development, financial assistance programs, healthcare improvements, and the creation of support networks for women. By addressing these challenges, women's empowerment in Palayamkottai can be enhanced, contributing to the region's overall development.